Transcendence and freely chosen constraints. Issue 2 (March 2019) - Gill, Robin
Four areas that can evoke a sense of transcendence are explored – music, marriage, intellectual discipline and worship – and affinities (and differences) are traced between religious and non-religious responses to the first three. Worship, however, is seen as especially distinctive for those who are religious.